2018
DOI: 10.1128/aem.00604-18
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-Hydroxybutyrate) (PHB) Polymerase PhaC1 and PHB Depolymerase PhaZa1 of Ralstonia eutropha Are Phosphorylated In Vivo

Abstract: In this study, we screened PHB synthase PhaC1 and PHB depolymerase PhaZa1 of for the presence of phosphorylated residues during the PHB accumulation and PHB degradation phase. Thr373 of PHB synthase PhaC1 was phosphorylated in the stationary growth phase but was not modified in the exponential and PHB accumulation phases. Ser35 of PHB depolymerase PhaZa1 was identified in phosphorylated form both in the exponential and in the stationary growth phase. Additional phosphosites were identified for both proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Polyhydroxyalkanoates (PHAs) are bacterial storage polyesters, which are currently used as a biobased replacement for some petroleum-derived plastics ( Surendran et al, 2020 ; Zheng et al, 2020 ). PHAs have attracted considerable interest in recent years for their potential as a biodegradable material ( Morohoshi et al, 2018 , 2020 ), since the polymers degrade well in the environment by the action of PHA depolymerases ( Juengert et al, 2018 ). PHAs possess diverse structures due to their variety in monomer constituents and their copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydroxyalkanoates (PHAs) are bacterial storage polyesters, which are currently used as a biobased replacement for some petroleum-derived plastics ( Surendran et al, 2020 ; Zheng et al, 2020 ). PHAs have attracted considerable interest in recent years for their potential as a biodegradable material ( Morohoshi et al, 2018 , 2020 ), since the polymers degrade well in the environment by the action of PHA depolymerases ( Juengert et al, 2018 ). PHAs possess diverse structures due to their variety in monomer constituents and their copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the fact that the amount of PHB synthesized by OfkbU during the exponential phase was not increased, so there was no more PHB available for degradation during the stationary phase. Previous studies reported that PHB synthase and depolymerase are simultaneously expressed in most PHB-accumulating strains, such as Ralstonia eutropha H16, but their activities are stringently regulated to avoid ineffective circulation [ 29 , 30 ]. Therefore, the combined overexpression of the PHB synthesis gene and decomposition gene in strain FS35 was deemed a reasonable approach.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the double knockout mutant spoT1 + spoT2 accumulated negligible amounts of PHB. In a subsequent work, Juengert et al (2018) identified that PhaC1 was phosphorylated in multiple phosphosites during the stationary growth phase in nutrient broth medium with gluconate as carbon source, but it was not modified during the exponential and PHB accumulation phases or when grown in a fructose-mineral medium. On the other hand, PhaZa1 was phosphorylated in Ser35 both during the exponential and stationary growth phases.…”
Section: Accumulation and Mobilization Of Phasmentioning
confidence: 98%